THE PERTINENCE AND IMPLEMENTATION OF IBN KHALDUN'S HISTORICAL PHILOSOPHICAL THOUGHT IN CONTEMPORARY SOCIETY - Faishal, Muhammad (University of Islam Malang, 2024)
The objective of this research is to ascertain the contemporary relevance of the historical philosophical ideas put forth by Ibn Khaldun. This research employs the historical method, with a literature review serving as the research subject and data collection instrument. When composing articles, both primary and secondary sources are utilized. The primary reference utilized is the Indonesian translation of Ibnu Khaldun's Muqaddimah. The author consults archival materials and periodicals whose titles correspond to those of the secondary sources. The research findings comprised the musings of Ibnu Khaldun as presented in his book Muqaddimah, which provides insights into historical knowledge regarding civilization and social society. Ibn Khaldun actually criticized history in his philosophy of history by cautioning against hastening to believe the news. Appropriate for the current era, in which false news is frequently encountered. Ibn Khaldun's method must be applied to ensure that no historical falsities exist.